Martini 3 Coarse‐Grained Force Field: Small Molecules. Issue 1 (30th December 2021) - Alessandri, Riccardo; Barnoud, Jonathan; Gertsen, Anders S.; Patmanidis, Ilias; de Vries, Alex H.; Souza, Paulo C. T.; Marrink, Siewert J.
Abstract: The recent re‐parametrization of the Martini coarse‐grained force field, Martini 3, improved the accuracy of the model in predicting molecular packing and interactions in molecular dynamics simulations. Here, we describe how small molecules can be accurately parametrized within the Martini 3 framework and present a database of validated small molecule models. We pay particular attention to the description of aliphatic and aromatic ring‐like structures, which are ubiquitous in small molecules such as solvents and drugs or in building blocks constituting macromolecules such as proteins and synthetic polymers. In Martini 3, ring‐like structures are described by models that use higher resolution coarse‐grained particles (small and tiny particles). As such, the present database constitutes one of the cornerstones of the calibration of the new Martini 3 small and tiny particle sizes. The models show excellent partitioning behavior and solvent properties. Miscibility trends between different bulk phases are also captured, completing the set of thermodynamic properties considered during the parametrization. We also show how the new bead sizes allow for a good representation of molecular volume, which translates into better structural properties such as stacking distances. We further present design strategies to build Martini 3 models for small molecules of increased complexity. Abstract : We describe how small molecules can be accurately parametrized within the recently developed Martini 3 coarse‐grained force field and present a database of validated small molecule models. The database, along with the outlined model design strategies and the modularity of the Martini force field, pave the way for the investigation of complex biomolecular and soft material systems.